Giving Voice to the Trans Community on GID Reform in the DSM-5: A Saskatchewan Perspective - Richards, Jai T. (Canadian Journal of Counselling and Psychotherapy, 2012)
The inclusion of the diagnosis of gender identity disorder (GID) within the Diagnostic and Statistical Manual of Mental Disorders (DSM) is a contentious issue. A summary of the arguments for retention, removal, or reform of the diagnosis in the DSM-5 is presented. A qualitative study with 7 individuals from Saskatchewan, Canada, was conducted. They discussed being diagnosed with a “disorder,” their experience of being transgender in Saskatchewan, and their opinions about the current debate. There is a discussion of the themes from the interviews. The implications for counsellors and other health providers and recommendations for further inquiry are also presented.